2022
DOI: 10.1097/md.0000000000030814
|View full text |Cite
|
Sign up to set email alerts
|

A case report of possible concurrent vasculitis in vertebral bodies and partial transverse myelitis following COVID-19 vaccination

Abstract: Introduction: Cases with organ-specific and systemic vasculitis associated with corona virus disease 2019 (COVID-19) vaccination have been reported. However, acute partial transverse myelitis (APTM) is rare adverse events following received COVID-19 vaccines. To the best of our knowledge, there is no report on vaccine-associated APTM accompanied by possible concurrent vasculitis. Herein we present a case with possible concurrent spinal vasculitis and APTM following the second dose of inactivated COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Hirose et al [ 57 ] and Eom et al [ 58 ] described cases of ATM following mRNA-1273 (Moderna) and Pfizer-BioNTech vaccination, respectively. Alabkal et al [ 59 ] reported a case of TM following the Pfizer-BioNTech vaccine, while Chen et al [ 60 ] described a concurrent vasculitis in vertebral bodies and partial TM in a patient whose vaccine type was not specified. These cases add further evidence to the potential association between COVID-19 vaccination and the development of ATM or TM.…”
Section: Discussionmentioning
confidence: 99%
“…Hirose et al [ 57 ] and Eom et al [ 58 ] described cases of ATM following mRNA-1273 (Moderna) and Pfizer-BioNTech vaccination, respectively. Alabkal et al [ 59 ] reported a case of TM following the Pfizer-BioNTech vaccine, while Chen et al [ 60 ] described a concurrent vasculitis in vertebral bodies and partial TM in a patient whose vaccine type was not specified. These cases add further evidence to the potential association between COVID-19 vaccination and the development of ATM or TM.…”
Section: Discussionmentioning
confidence: 99%